Study of the Stability of Factor VIII Activity in Human Plasma for Fractionation When Modeling Deviations in the Storage and Transportation Temperature Conditions - A. A. Gorodkov; A. L. Poptsov; A. L. Khokhryakov (Биопрепараты: Профилактика, диагностика, лечение, 2020)
The European Pharmacopoeia requires that the transportation and storage of human plasma for fractionation should be carried out at –20 °C or below, while allowing for some deviations in the temperature regime. The current Russian regulatory documentation requires the transportation and storage of plasma intended for the production of labile protein preparations (blood clotting factors) at  –30 °C or lower. However, acceptable deviations from the temperature regime are not specified, which creates certain difficulties in their assessment by an authorised person during plasma batch release. The main tool in risk assessment is in-process control of factor VIII activity in plasma stored at inadequate temperature, which entails significant financial costs. The aim of the study was to assess stability of factor VIII activity in human plasma for fractionation when modeling deviations in the storage and transportation temperature regime and to assess the possibility of amending the regulatory documentation requirements. Materials and methods: only full individual doses of plasma obtained by apheresis were used in the experiments. The tests were performed under simulated high temperature conditions with accurate continuous recording of temperature by a measuring system. An automatic coagulation analyser was used to determine factor VIII activity. Quantitative evaluation of the results was carried out by comparing factor VIII activity in the plasma before freezing and in the tested plasma. Statistical processing of data was performed by descriptive statistics methods using Microsoft Excel 2007 applications. Results: no significant effect of short-term deviations in the storage temperature on the stability of factor VIII activity in human plasma for fractionation was observed. Conclusions: the obtained data can be used as a rationale for introducing changes in the official requirements for the storage and transportation temperature regime for human plasma for fractionation, as well as for including details of acceptable short-term deviations of the storage and transportation temperature regime in the regulatory documentation.